2018
DOI: 10.1007/s13197-018-3201-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in vitro assessment of potential probiotic characteristics and antibacterial effects of Lactobacillus plantarum subsp. plantarum SKI19, a bacteriocinogenic strain isolated from Thai fermented pork sausage

Abstract: A total of 2257 lactic acid bacteria were preliminarily screened for antagonistic activity against subsp. JCM 1157. Strain SKI19 was selected and identified at the subspecies level as subsp. SKI19, using rRNA gene sequence analysis combined with and genes' amplification. Antibacterial activity of SKI19 was completely lost after treatment of neutralized cell free culture supernatant with proteolytic enzymes, suggesting that SKI19 produced a bacteriocin-like substance that inhibited not only closely related spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The cell surface hydrophobicity of the isolates was tested according to the method described by Botthoulath et al (2018) [20] with slight modification. It helps us understand the interaction between xylene (polar solvent) and the bacteria.…”
Section: Adherence Assay Cell Surface Hydrophobicitymentioning
confidence: 99%
“…The cell surface hydrophobicity of the isolates was tested according to the method described by Botthoulath et al (2018) [20] with slight modification. It helps us understand the interaction between xylene (polar solvent) and the bacteria.…”
Section: Adherence Assay Cell Surface Hydrophobicitymentioning
confidence: 99%
“…4 The diameter of starch hydrolysis halos (mm) and inhibition halos (mm) of Lactobacillus brevis isolates (Lb1-Lb12) against Bacillus cereus, Escherichia coli, and Salmonella Typhimurium by the spot-on-lawn method LAB, which can decrease the pH of the medium to values low enough to inhibit the growth of most pathogenic and deteriorating microorganisms. However, some authors report that some strains of L. plantarum can be bacteriocinogenic (Botthoulath et al 2018).…”
Section: Selection Of Lactic Acid Bacteria For Use As Starter Culturesmentioning
confidence: 99%
“…Costa et al (2013) reported that the addition of L. plantarum to bekasam meat produced a higher lactic acid that would inhibit the growth of E. coli and S. aureus. Similarly, Botthoulath et al (2018) found an inhibitory activity in fermented pork sausage against E. coli DMST 4212 and S. aureus DMST 8840, as the pathogen cell counts fell rapidly by approximately 3 log units at 24 h, and further to below detection limit after 36 h of incubation. The production of bekasam meat using grampositive lactic acid bacteria (L. plantarum) would produce a zone of inhibition to the growth of pathogenic bacteria (Gloria et al, 2012;Wang et al, 2018).…”
Section: Microbiological Analysismentioning
confidence: 79%